Comparative Evaluation of Aqueous Leaf Extracts and Latex of Eleaphorbia Drupifera - E. A., Okon; E. U., Umoh; P. M., Bobson; I. G., Etim; I. U., Sunday (American Journal of Bioscience and Clinical Integrity, 2024)
This study investigated the comparative evaluation of aqueous leaf extracts and latex of Eleaphorbia drupifera, and analysis was carried out both qualitatively and quantitatively. The crude extract of the leaves and latex from Eleaphorbia drupifera were prepared using standard methods. The phytochemical constituents and mineral composition of the leaves and latex of Eleaphorbia drupifera were determined qualitatively and quantitatively with the view to assess their therapeutic potential or potency as well as safety/toxicity of the plant in traditional Medicine (ethnomedicine). The results of elemental analysis of the leaf extract revealed the presence of Mg (34.66mg/L), Na (56.42mg/L), Ca (135.37mg/L), Zn (106.22mg/L), Mn (94.32mg/L), Fe(77.45mg/L), Pb(0.003mg/L), Co and Hg were in trace amount while Cd was not detected. The elemental analysis of the latex showed the presence of Mg (21.72mg/L), Na (33.22mg/L), Ca (116.60mg/L), Zn (97.22mg/L), Mn(72.32mg/L), Fe(77.18mg/L), Co (3.56mg/L), Pb(25.18mg/L), Hg in trace amount and Cd not detected. However, the proximate analysis carried out on the aqueous leaf extract indicated moisture content (65%), ash (6%), crude fibre (3%), crude fat (2.5%), crude protein (1.8%), available carbohydrate (21.70%). Whereas latex indicated moisture content (77%), ash (4.5%), crude fibre (2%), crude fat (3.5%), crude protein (2.45%), available carbohydrate (14.55%), Anti-nutrient contents of the leaf extract were oxalate (0.81mg/100g), hydrogen cyanide (0.42mg/100g) and phytate (0.0062mg/100g) whereas latex had oxalate (0.73mg/100g), hydrogen cyanide (0.42mg/100g) and Phytate (0.005mg/100g). However, the quantitative estimation of the phytochemical compositions of the latex showed, the concentration of alkaloid (0.15mg/100g), saponin (0.3mg/100g), polyphenol (0.08mg/100g), while the leaf indicated flavonoids (0.21mg/100g), cardiac glycoside (0.055mg/100g) and reducing sugar (0.03mg/100g). Tannins, phlobatannins, anthranoids and anthraquinones were absent. It is concluded that the aqueous leaf extracts and latex of Eleaphorbia drupifera are made up of useful bioactive compounds that could play remarkable role in health and treatment of disease.